Improving Digital Literacy for Class Xi Students of ST Catholic Vocational School. Willibrodus Betun Through the Use of Evernote Educational Software - Nae, Angela Prima; Taku Neno, Khatrin J.; A. Benufinit, Yonly (JUPE : Jurnal Pendidikan Mandala, 2024)
Angela Nae, 2024. Improving Digital Literacy for Class XI Students at St. Catholic Vocational School. Willibrodus Betun. Through the Use of Evernote Educational Software. Thesis, Informatics Education Study Program. Citra Bangsa University. Advisor Khatrin J. Taku Neno, S.Pd Kom., M.Pd & Yonly A. Benufinit, S.Kom., M.TThe purpose of this study is to ascertain how St. Catholic Vocational School students in class XI use digital literacy improvement. Betun Willibrodus Using the Educational Software Evernote. The research methodology makes use of experimental and quantitative research techniques. All St. Catholic Vocational School class XI TKJ pupils made up the study's population. Betun Willibrodus. A two-group post-test design model was used for sampling, with class XI TKJ 1 serving as the experimental group and XI TKJ 2 as the control group. Student questionnaires and multiple-choice exams were the tools utilized.The data analysis method makes use of the independent t-test. According to the study data, the experimental group's average posttest scores were 89.6 and 40.4, respectively, and the control group's average percentage of the research questionnaire was 96.28%. The results of the t-test analysis indicate a significant value of 0.000 <0.05, indicating that Ha is accepted and H0 is rejected in accordance with the criteria employed to formulate the hypothesis.The data analysis method makes use of the independent t-test..The results of the study showed that the experimental and control groups completed 96.28% of the research questionnaire on average, and their average posttest scores were 89.6 and 40.4, respectively. The results of the t-test analysis indicate a significant value of 0.000 <0.05, indicating that Ha is accepted and H0 is rejected in accordance with the criteria employed to formulate the hypothesis. According to the study's findings, St. Catholic Vocational School's class XI TKJ students were using Evernote educational software to improve their digital literacy. Betun Willibrodus.